2008
DOI: 10.1211/ijpp.16.5.0009
|View full text |Cite
|
Sign up to set email alerts
|

Using suitability profiles to better inform consumers' choice of commonly used over-the-counter analgesics

Abstract: Objective To quantify the impact of labelled contraindications, precautions and warnings for use on the population that may take commonly used over‐the‐counter (OTC) analgesics. Setting Primary care: data were collected from a general practitioner database in Australia. Methods Patient data were audited retrospectively (n = 107553) to determine the number of patients with contraindications, warnings or precautions to the use of OTC paracetamol and the non‐steroidal anti‐inflammatory drugs aspirin and ibuprofen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
(2 reference statements)
1
3
0
Order By: Relevance
“…The quality use of medicines, in particular OTC NSAIDs, is becoming increasingly reliant on product labelling and the ability of consumers to understand and self‐assess risk. Our suitability‐rate data are consistent with previous patient data research conducted among Australian general practitioners [7] …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The quality use of medicines, in particular OTC NSAIDs, is becoming increasingly reliant on product labelling and the ability of consumers to understand and self‐assess risk. Our suitability‐rate data are consistent with previous patient data research conducted among Australian general practitioners [7] …”
Section: Discussionsupporting
confidence: 89%
“…The age‐interactions‐medications (AIM) protocol is a simple screening tool designed to ensure appropriate use of OTC analgesics [7] . Applying the first of the principles set out in this tool (age) to our consumer data it is noteworthy that, despite the rise in OTC NSAID use, the proportion of elderly patients (aged 65 years or more) currently using these compounds is minimal (2.0%) and that paracetamol use has increased among the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is remarkable, because older patients are more prone to adverse drug reactions, especially in the case of comedication or of comorbidities such as liver or kidney failure. An Australian study found that for over-the-counter medication, 1.9% of paracetamol users and 23.1% of ibuprofen users had contraindications for these analgesics [36]. In another open population, it was shown that 10% of older patients with low back pain used NSAIDs while they were also using a diuretic and an angiotensin-converting enzyme inhibitor or angiotensin II receptor antagonist [35]; such patients are at increased risk of acute renal failure [37].…”
Section: Interpretation Of Findingsmentioning
confidence: 99%